2014
DOI: 10.1021/jf500739n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Conditions on the Organosulfides of Shallot (Allium cepa L. Aggregatum Group)

Abstract: There is a growing account of the health benefits of H2S as an endogenous cell-signaling molecule. H2S from organic polysulfides, in particular, is increasingly gaining attention for their beneficial effects to cardiovascular health. Here, we studied shallot as a potential dietary source of organic polysulfides and examined the effects of processing conditions on its polysulfide profiles. Boiling, autoclaving, and freeze-drying were tested on whole and crushed shallot bulbs, analyzing their effect on the yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
3
19
0
7
Order By: Relevance
“…Our results were also in agreement with a literature report on distilled garlic oil showing favoured formation of disulphides at pH 9.0 while trisulphides were much higher at weakly acidic pH range (Yu, Wu, & Chen, 1989). Recently, we demonstrated similar trends on the pH sensitivity of polysulphides in shallot oil (Tocmo, Lin, & Huang, 2014). It has been suggested that optimal formations of trisulphides at acidic pH could be due to their stability and the stability of alliinase in this pH range under heat treatment (Yu et al, 1989).…”
Section: Effect Of Ph On the Organosulphide Profiles Of Garlic Scape Oilsupporting
confidence: 70%
“…Our results were also in agreement with a literature report on distilled garlic oil showing favoured formation of disulphides at pH 9.0 while trisulphides were much higher at weakly acidic pH range (Yu, Wu, & Chen, 1989). Recently, we demonstrated similar trends on the pH sensitivity of polysulphides in shallot oil (Tocmo, Lin, & Huang, 2014). It has been suggested that optimal formations of trisulphides at acidic pH could be due to their stability and the stability of alliinase in this pH range under heat treatment (Yu et al, 1989).…”
Section: Effect Of Ph On the Organosulphide Profiles Of Garlic Scape Oilsupporting
confidence: 70%
“…al. (2014), showed that thermal processing by both boiling and autoclaving resulted in significant losses in cyclic and acyclic organosulfides in shallot (Allium cepa L. Aggregatum Group), whilst freeze-drying retained the majority of the organosulfides, although some were found to be sensitive towards freeze-drying as well (Tocmo et al, 2014). These drying methods (air-, oven-and freeze-drying) were also shown to significantly affect the yield and composition of the essential oils obtained by hydrodistillation of the dried garlic bulbs, with freeze-drying resulting in a much higher yield of diallyl tetrasulfide and diallyl trisulfide (Dziri et al, 2014).…”
Section: )mentioning
confidence: 99%
“…There are few reports regarding the analysis of these compounds in cooked garlic samples (Cavagnaro, Camargo, Galmarini, & Simon, 2007;Kim, Wu, Kobayashi, et al, 1995;Kim, Wu, Kubota, & Kobayashil, 1995;Yu & Wu, 1994;Yu et al, 1993). Works reported have been based on the analysis of OSCs by GC-MS (Artacho Martin-Lagos, Olea Serrano, & Ruiz Lopez, 1995;Tocmo, Lin, & Huang, 2014;Yan, Wang, & Barlow, 1992, using Lickens-Nickerson distillation and solvent extraction techniques (Kim, Wu, Kobayashi, et al, 1995;Yu et al, 1993Yu & Wu, 1994;Yu, Wu, & Chen, 1989;Yu, Wu, & Liou, 1989). It is worth emphasizing that those sample preparation techniques, as well as the subsequent analysis by GC, are inadvisable (Block, Putman, & Zhao, 1992).…”
Section: Introductionmentioning
confidence: 99%